Contemporary French Fiction In and Out of Screens - Eliane DalMolin (Studies in 20th & 21st Century Literature, 2012)
This essay explores the ways in which the widespread craze for reality TV has now extended its contamination to the comparatively more traditional discipline of literature. Today, there is no use denying that, acknowledging, and internalizing, the American domination in the creation of reality shows, French television has followed suit and, as a result of the cultural flooding of such a model, recent French literature has also been swayed by the empire of television in general, and the power of reality TV in particular. The author delineates the increasingly porous frontier separating and conjoining reality TV and literary representation, questions the adoption and consecration of banality as the basic principle of this porosity, and examines the consequences of such a sustained exposure to images of a trite reality on the quality of traditional cultural artifacts such as books. Among other aspects of this transfer, the essay focuses on the effect of the strange and voyeuristic interdependence of cameras, men and their plain reality. Ultimately, the essay wonders why, in all forms of cultural representation, high or low, a spectacle of great banality has now been elevated to the rank of acclaimed cultural production.
Keywords: French fiction; reality TV; French literature; culture; literary representation